Respond Characteristic Property in Different Temperatures of SAW Sensor with p-Tertbutylcalix[4] Coatings to Detect Sarin - Cao*, Bingqing; Huang, Qibin; Qing, Molin (Asian Journal of Chemistry, 2014)
25-(Thioalkyl-alkoxy)-p-tertbutylcalix[4]arene self-assembly molecular imprinted film as the sensitive film was coated on the gold delay line of SAW sensors to detect the orgnaophosphorous analogue compounds such as sarin. The sensor has special response to organoosphorus compounds and the response frequency shift of this sensor to organosphorus compounds. The possible explanation of interactions between the coatings and organosphorus compounds is discussed. The results indicated that the SAW sensor coated with self-assembled monolayers character had high sensitivity to sarin, faster response, repetition and had important reference value in future practical application.